Hubungan Pengetahuan dan Peran Petugas Kesehatan Dengan Pencegahan Penyebaran Virus Covid-19 di RW 002 Kelurahan Raha III Kecamatan Katobu Kabupaten Muna - Nursiah Nursiah; Taswin; Fitriani; Dahmar (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Coronavirus 2019 (Covid-19) is an infectious disease caused by coronavirus 2 (SarsCoV2) which causes acute respiratory syndrome. Data from the Muna Health Service until early November said 124 were confirmed positive for the Covid-19 virus and 19 of them were residents of Raha III District. The purpose of this study was to determine the relationship between knowledge and the role of health workers with preventing the spread of the Covid-19 virus in RW 002, Raha III Village. This study used a cross sectional study design with accidental sampling as many as 284 respondents in RW 002 Kelurahan Raha III. Analysis of quantitative data using the chi-square relationship test. The research instrument used a questionnaire. The results showed that there was a relationship between knowledge (p value = 0.000 < 0.05), and the role of health workers (p value = 0.000 < 0.05) with preventing the spread of the Covid-19 virus in RW 002 Kelurahan Raha III. The conclusion in this study is that there is a relationship between knowledge and the role of health workers with preventing the spread of the Covid-19 virus in RW 002, Raha III Village. This research is expected to increase public knowledge and be able to better comply with the Covid-19 protocol as recommended by the government.